New data on the Lepidoptera of Azerbaijan (Southern Transcaucasia). Superfamily Pyraloidea Latreille, 1809 - Aleksandr N. Streltzov; Nataly Snegovaya; Nazar A. Shapoval; Mahmud F.-O. Humbatov; Ismayil B.-O. Mammadov; Roman V. Yakovlev (Acta Biologica Sibirica, 2024)
We present the faunal list of Pyraloidea (Lepidoptera) of Azerbaijan, including 222 species of 114 genera, belonging to two families. Forty eight species of Pyraloidea Moths are reported for Azerbaijan for the first time.